Empowering Women Entrepreneurs in a Globalized Era: A Focus on North East India - Chanambam Nalini Devi (Journal for ReAttach Therapy and Developmental Diversities, 2022)
In the contemporary globalized landscape, women entrepreneurs in India, particularly in the region of North East India, navigate a complex interplay of opportunities and challenges influenced by rapid technological advancements and integration into international markets. This review investigates the pivotal factors that shape the empowerment of women entrepreneurs in this context, with a focused exploration on the specific barriers they face, the support mechanisms available to them, and the policy implications crucial for their advancement. Geographically isolated and characterized by diverse cultural norms, North East India presents unique challenges such as infrastructural limitations and traditional gender roles that affect women's access to resources and entrepreneurial opportunities. Despite these challenges, initiatives by governmental bodies, non-governmental organizations, and community-driven efforts play a pivotal role in providing financial support, skill development, and networking platforms tailored to enhance the entrepreneurial capabilities of women in this region. Effective policy interventions aimed at promoting gender equality, improving infrastructure, and fostering a propitious business environment are essential to bolstering women entrepreneurs' participation and success in the globalized economy, thereby driving sustainable economic growth and social development in North East India.